Processing and presentation of self and foreign antigens by the renal proximal tubule. - David Hagerty; Paul M. Allen (1992)
The renal proximal tubule (PT) in many ways resembles an APC. The PT is one of the few epithelial cells in the body reported to constitutively express the class II MHC molecules required to present Ag to CD4+ T cells. We questioned whether the PT could function as an APC in vitro and in vivo. Fluorescence cytometry demonstrated that the normal CBA/J PT constitutively expressed low levels of class II MHC and that this expression was markedly augmented by either IFN-gamma or systemic Listeria monocytogenes infection. Functionally, the PT from normal CBA/J mice also stimulated T cell hybridomas when cultured in vitro with Ag, and this ability was markedly up-regulated by both IFN-gamma as well as L. monocytogenes infection. To prove that the PT constitutively processed and presented self Ag in vivo, freshly isolated PT from mice transgenic for human alpha 1-antitrypsin were cultured with the appropriate T cell hybridoma in the absence of exogenous Ag. Strong stimulation of the T cell hybridoma occurred. Our data show that the renal proximal tubule processes and presents foreign Ag both in vitro and in vivo, and that it constitutively processes and presents the self Ag hAAT in vivo. These results have important implications for the understanding of renal interstitial autoimmune diseases as well as the interstitial nephritis that occurs in response to foreign Ag.